2018
DOI: 10.1049/iet-rpg.2018.5283
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of the effects of sonication time and volume concentration on the performance of PVT solar collector

Abstract: In this research, the effects of sonication time and volume concentration of cupric oxide (CuO)/water nanofluids on the thermal conductivity, viscosity and performance of photovoltaic-thermal (PVT) solar collector are investigated experimentally. Pure water, 0.05, 0.1 and 0.2% volume concentrations of CuO/water nanofluids prepared with 1, 2, 3 and 4 h sonication time are used as the heat transfer fluids in this study. The experimental results show that the thermal conductivity and viscosity of nanofluids are t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The influence of sonication time (1-4 h) on the κ, µ, outlet temperature, electrical, and thermal efficiency of CuO/DW NFs (0.05-0.2 vol%) as coolants in a photovoltaic-thermal solar collector is studied [182]. The results reveal that an increase in the sonication time causes an increase in κ (3.5%), outlet temperature (>65 • C), thermal and electrical efficiency, and a decrease in µ, all as functions of volume concentration.…”
Section: Thermal Performance Of Heat Transfer Devicesmentioning
confidence: 99%
“…The influence of sonication time (1-4 h) on the κ, µ, outlet temperature, electrical, and thermal efficiency of CuO/DW NFs (0.05-0.2 vol%) as coolants in a photovoltaic-thermal solar collector is studied [182]. The results reveal that an increase in the sonication time causes an increase in κ (3.5%), outlet temperature (>65 • C), thermal and electrical efficiency, and a decrease in µ, all as functions of volume concentration.…”
Section: Thermal Performance Of Heat Transfer Devicesmentioning
confidence: 99%
“…The outer cylinder rotates, the inner one is stationary, and measurements of it are taken. Rajendiram et al [51] studied the effect of sonication on viscosity and thermal conduction. For viscosity, a cone-plate viscometer was used, which observed that the longer the exposure time, the lower the viscosity and the greater the thermal conductivity.…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…Globally, in 2023, the PV/T collector area reached 1.5 million m 2 , equivalent to a thermal capacity of 789 MW and an electrical capacity of 276 MWp [8]. This PV/T system, when integrated into buildings and used by the building for both electricity and thermal energy, is referred to as the BIPV/T system [9]. Due to being relatively new emerging systems worldwide, the use of BIPV and BIPV/T systems continues to increase annually.…”
Section: Introductionmentioning
confidence: 99%